Upaya Meningkatkan Motivasi Belajar Siswa melalui Strategi Pembelajaran Resource Based Learning (RBL) dalam Pembelajaran IPA Kelas V di SD Negeri 08 Kurnia Maju - Pardi Ramadhan; Ibsan Ramadhani; Donny Firdaus; Lopianda Lopianda (JURNAL ILMIAH PENELITIAN MAHASISWA, 2024)
The background of the research is that student learning motivation is low in the science learning process. This can be seen during learning activities, only 8-9 students are active even though the total number of students in grade V is 29 people. The rest of the students seem less enthusiastic in learning activities due to various factors, namely: students tend to be bored following the lesson, students do not master the material. With this learning model, it will help students think about the material independently and creatively. This type of research is Classroom Action Research (CAR). The research subjects are 29 students of grade V of SD Negeri 08 Kurnia Maju. The results of this study indicate that the Resource Based Learning (RBL) strategy that has been carried out can increase student learning motivation in Natural Sciences (IPA) learning. This can be seen from the overall score of student learning motivation in cycle I of 58.02% which is in the medium category. Then in cycle II it increased again to 67.30% which is in the high category. So it can be said that the actions that have been carried out are in accordance with what is expected.